Need for a safe vaccine against respiratory syncytial virus infection - Joo-Young Kim; Jun Chang (Korean Pediatric Society, 2012)
Human respiratory syncytial virus (HRSV) is a major cause of severe respiratory tract illnesses in infants and young children worldwide. Despite its importance as a respiratory pathogen, there is currently no licensed vaccine for HRSV. Following failure of the initial trial of formalin-inactivated virus particle vaccine, continuous efforts have been made for the development of safe and efficacious vaccines against HRSV. However, several obstacles persist that delay the development of HRSV vaccine, such as the immature immune system of newborn infants and the possible Th2-biased immune responses leading to subsequent vaccine-enhanced diseases. Many HRSV vaccine strategies are currently being developed and evaluated, including live-attenuated viruses, subunit-based, and vector-based candidates. In this review, the current HRSV vaccines are overviewed and the safety issues regarding asthma and vaccine-induced pathology are discussed.